Relative Fitness and Feeding Capacity of Imidacloprid Resistant Nilaparvata lugens - Jesayas A. Londingkene; Y. Andi Trisyono; Witjaksono Witjaksono; Edhi Martono (Jurnal Perlindungan Tanaman Indonesia, 2016)
Imidacloprid is a neonicotinoid insecticide that is recommended for controlling Nilaparvata lugens. In Asian countries, such as, China, Vietnam, India, and Thailand, imidacloprid has caused resistance to N. lugens. Imidacloprid has also caused resistance to N. lugens based on some previous studies in Indonesia. The aim of this study was to determine the fitness and feeding capacity of imidacloprid-resistant N. lugens. The population of N. lugens used in this study had a resistance level of 50.64 times compared to the susceptible population. When the resistant and susceptible population of N. lugens did not receive any exposure to imidacloprid, the susceptible population had better fitness than the resistance one. However, the fitness of the resistant population increased when this population was resistance which sublethal cencentration (LC50 & LC20) of imidacloprid. The increase fitness of this resistant population most likely related to the increase in feeding capacity of the resistant population when they were treated which sublethal imidacloprid. These findings suggest that the field population of N. lugens that have developed resistance would increase the probability of outbreak if they were sprayed with imidacloprid. INTISARI Imidakloprid adalah insektisida neonicotinoid yang direkomendasikan untuk mengendalikan Nilaparvata lugens. Di negara Asia, seperti, China, Vietnam, India, dan Thailand, imidakloprid telah menyebabkan resistensi terhadap N. lugens. Di Indonesia, berdasarkan beberapa penelitian sebelumnya dilaporkan imidakloprid juga menyebabkan resistensi terhadap N. lugens. Tujuan penelitian ini untuk mengetahui kebugaran relatif dan kemampuan makan N. lugens resisten terhadap imidakloprid. Populasi N. lugens yang digunakan dalam penelitian ini mempunyai tingkat resistensi 50,64 kali dibandingkan dengan populasi peka. N. lugens populasi resisten dan peka apabila tidak dipapar dengan imidakloprid, populasi peka mempunyai kebugaran lebih baik dari pada resisten, namun kebugaran dari N. lugens populasi resisten meningkat ketika populasi tersebut dipapar dengan imidakloprid konsentrasi subletaal (LC50 & LC20). Peningkatan kebugaran populasi N. lugens resisten diduga terkait dengan peningkatan kemampuan makan akibat dipapar lagi dengan imidakloprid subletal. Hasil penelitian ini menunjukkan bahwa ledakan N. lugens akan terjadi, apabila populasi N. lugens yang telah resisten terhadap imidakloprid dipapar lagi dengan imidakloprid.